2018
DOI: 10.3349/ymj.2018.59.3.397
|View full text |Cite
|
Sign up to set email alerts
|

Delta Neutrophil Index Is Associated with Vasculitis Activity and Risk of Relapse in ANCA-Associated Vasculitis

Abstract: PurposeDelta neutrophil index (DNI) represents the immature granulocytes count associated with neutrophil-consumption. We investigated whether DNI might be associated with Birmingham vasculitis activity score (BVAS) at diagnosis and could predict relapse during the follow-up in patients with antineutrophil cytoplasmic antibody-associated vasculitis (AAV).Materials and MethodsWe reviewed the medical records of 97 patients having DNI results. Twenty patients had granulomatosis with polyangiitis (GPA), 58 had mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…The so called delta neutrophil index (DNI), a simultaneous view at the number of immature granulocytes and the consumption of neutrophil granulocytes, correlates with the Birmingham vasculitis activity score at diagnosis—an instrument which helps assessing disease activity in patients with PSV (97). DNI values ≥0.65% were shown to be a surrogate parameter for a difficult progression of AAV and relapse in GPA and MPA during the observation period (97). This connection may be the result of the following considerations: T cells and macrophages release inflammatory cytokines that prime neutrophils and cause an increase in adhesion molecules on neutrophils and endothelial cells.…”
Section: Small Vessel Vasculitismentioning
confidence: 99%
See 1 more Smart Citation
“…The so called delta neutrophil index (DNI), a simultaneous view at the number of immature granulocytes and the consumption of neutrophil granulocytes, correlates with the Birmingham vasculitis activity score at diagnosis—an instrument which helps assessing disease activity in patients with PSV (97). DNI values ≥0.65% were shown to be a surrogate parameter for a difficult progression of AAV and relapse in GPA and MPA during the observation period (97). This connection may be the result of the following considerations: T cells and macrophages release inflammatory cytokines that prime neutrophils and cause an increase in adhesion molecules on neutrophils and endothelial cells.…”
Section: Small Vessel Vasculitismentioning
confidence: 99%
“…ANCA promote the interaction of neutrophils and endothelial cells, which results in the diapedesis of neutrophils through the vascular cell layers. Finally, activated neutrophils induce vasculitis by reactive oxygen radicals and degranulation (97104).…”
Section: Small Vessel Vasculitismentioning
confidence: 99%
“…We previously aimed to identify the clinical significance of certain independent baseline factors in predicting the poor outcomes of AAV, while considering these ethnic differences in disease presentation. All-cause mortality has been shown to be positively and inversely associated with the C-reactive protein (CRP)-to-serum albumin and the albumin-to-globulin ratios at diagnosis, respectively,89 while AAV-relapse has been found to be associated with the neutrophil-to-lymphocyte ratio, delta neutrophil index, and systemic immune-inflammation index at diagnosis 101112. Similarly, development of ESRD is known to be associated with systemic immune-inflammation and low levels of complement 3 at diagnosis 1213.…”
Section: Introductionmentioning
confidence: 99%
“…DNI has been reported to be associated with conditions, in which mature neutrophils are consumed, such as sepsis and disseminated intravascular coagulation 71. Recently, Yoo, et al72 suggested a association between DNI and either current BVAS or relapse in 97 Korean patients with AAV. They indicated that DNI could reflect current BVAS and that DNI ≥0.65% could predict a higher rate of relapse during follow-up of AAV.…”
Section: Indices At Diagnosis For Activity and Prognosismentioning
confidence: 99%